2021
DOI: 10.3389/fpubh.2021.748041
|View full text |Cite
|
Sign up to set email alerts
|

Government Epidemic Prevention and Economic Growth Path Under Public Health Emergency: Theoretical Model and Simulation Analysis

Abstract: This paper constructs a partial equilibrium model under public health emergency shocks based on economic growth theory, and investigates the relationship between government intervention and virus transmission and economic growth path. We found that both close contacts tracing measures and isolation measures are beneficial to human capital stock and economic output per capita, and the effect of close contact tracing measures is better than that of isolation measures. For infectious diseases of different intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Advancements in vaccines have played a major role in the significant decrease of exanthem infection cases globally and led to the eradication of multiple viral diseases; yet, the risk of outbreaks still exists ( “CDC,” 2024 ). Such outbreaks can lead to substantial health and socioeconomic burdens on countries ( Yin et al, 2021 ). Governmental policies, such as vaccine mandates, help in reducing and mitigating the risks of outbreaks and maintaining the overall health and well-being of the public.…”
Section: Exanthematous Viral Infectionsmentioning
confidence: 99%
“…Advancements in vaccines have played a major role in the significant decrease of exanthem infection cases globally and led to the eradication of multiple viral diseases; yet, the risk of outbreaks still exists ( “CDC,” 2024 ). Such outbreaks can lead to substantial health and socioeconomic burdens on countries ( Yin et al, 2021 ). Governmental policies, such as vaccine mandates, help in reducing and mitigating the risks of outbreaks and maintaining the overall health and well-being of the public.…”
Section: Exanthematous Viral Infectionsmentioning
confidence: 99%
“… 48 Yin et al constructed a local equilibrium model to analyze the impact of the government’s interventions on the social economy under infectious diseases with different intensities. 49 Roberts et al designed a set of sequential mediation models to find the key factors that influence college students’ behaviors and emphasized how individual self-protection can greatly reduce the rate of infection in the population. 50 …”
Section: Literature Reviewmentioning
confidence: 99%
“…48 Yin et al constructed a local equilibrium model to analyze the impact of the government's interventions on the social economy under infectious diseases with different intensities. 49 Roberts et al designed a set of sequential mediation models to find the key factors that influence college students' behaviors and emphasized how individual self-protection can greatly reduce the rate of infection in the population. 50 According to the above literature review, whistleblowers' active vocalization can make the public know more details about the risk posed by an event, increase its risk perception, and prompt the relevant departments to take appropriate measures.…”
Section: Risk Perception and Preventive Behaviorsmentioning
confidence: 99%
“…In the first stage (T = 0-16), the level of activity improves rapidly as the parameters expand. The indicator declines more significantly in line with the increased parameters in the second stage (T = [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and then tends to maintain stable growth with a reduced slope in the final stage (T = 36-69). In Figure 7c, the total social and economic benefit approximately maintains a linear increase over the whole duration of the pandemic, and in all cases, proportionally changes in line with the variation in the parameters.…”
Section: Sensitivity Analysis Of Model Parametersmentioning
confidence: 99%
“…The study concluded that removing anti-epidemic measures too early will result in large benefits in the short term, but will not achieve consistent benefits in the long run. Yin et al [ 31 ] studied the link between, on the one hand, government intervention and the spread of the pandemic and, on the other hand, economic development under conditions of public health emergency shocks. The results also demonstrate that strict anti-virus policy measures have a limited effect in recovering from the harmful impact of the public health emergencies caused by the highly contagious virus.…”
Section: Literature Reviewmentioning
confidence: 99%